PERMUTATION-BASED POLYMORPHIC STEGO-WATERMARKS FOR PROGRAM CODES - Samoilenko, Denys (Proceedings of National Aviation University (archive), 2016)
Purpose: One of the most actual trends in program code protection is code marking. The problem consists in creation of some digital “watermarks” which allow distinguishing different copies of the same program codes. Such marks could be useful for authority protection, for code copies numbering, for program propagation monitoring, for information security proposes in client-server communication processes. Methods: We used the methods of digital steganography adopted for program codes as text objects. The same-shape symbols method was transformed to same-semantic element method due to codes features which makes them different from ordinary texts. We use dynamic principle of marks forming making codes similar to be polymorphic. Results: We examined the combinatorial capacity of permutations possible in program codes. As a result it was shown that the set of 5-7 polymorphic variables is suitable for the most modern network applications. Marks creation and restoration algorithms where proposed and discussed. The main algorithm is based on full and partial permutations in variables names and its declaration order. Algorithm for partial permutation enumeration was optimized for calculation complexity. PHP code fragments which realize the algorithms were listed. Discussion: Methodic proposed in the work allows distinguishing of each client-server connection. In a case if a clone of some network resource was found the methodic could give information about included marks and thereby data on IP, date and time, authentication information of client copied the resource. Usage of polymorphic stego-watermarks should improve information security indexes in network communications.